BAHASA, NEGARA, DAN KEKUASAAN: STRUKTUR-KULTUR POLITIK KEBIJAKAN BAHASA INDONESIA - Pratama, Rony K. (Diksi, 2018)
(Title: Languages, State, and Power: Political Structures of Indonesian Policy). Language as a discipline has been established by the political preconditions and the re-sult is negotiating the power of the state. Its development is not entirely neutral because the tendency of language as a tool of power has a strong gap to be constructed in such a way. This epistemological reality then strengthens the reciprocal dictum between langua¬ge and power that can be hegemonically practiced as long as the state applies a system of rules in a systemic manner. This paper tries to investigate Indonesian language as a practice of state power, both projected historically, politically, and economically. All of them are covered by cultural narratives that are reinforced through structural patterns to culture.Keywords: language, country, power, policy, Indonesian language